Decentralization in the Philippines : Stgrengthening Local Government Financing and Resource Management in the Short Term - World Bank (Washington, DC, 2013)
This report reviews two facets of decentralization currently engaging policy-makers: 1) the sources of financing under decentralization, and, 2) cross-cutting processes to strengthen the accountability of resource use. It does not assess whether decentralization is justified in the Philippines - it approaches the arrangements as they exist, and explicitly focuses on actions that could be feasibly completed within six to nine months. Administrative actions in two key areas could improve local government performance in the short term: a) enhancing LGU - Local Government Unit - ability and capacity to access resources, and, (b) strengthening key resource management processes in the first instance, those relating to planning, budgeting, procurement and financial management. The report's recommendations stem from five main issues: raising LGU access to credit by private financial institutions (PFIs) requires removing bottlenecks to PFI participation in LGU lending, and rationalizing LGU grant policies; local government own-source revenues could be significantly increased through LGU measures to increase collection of real property tax and business tax, and, national government actions to assist LGUs; local government planning and budget management could be made more effective, transparent and accountable through administrative measures by local and national governments; actions to embed transparency and accountability within LGU procurement and financial management processes, could improve these processes, promote effective resource use, and strengthen LGU governance over time; and, the national government should initiate a review of the institutional arrangements for generating consensus among stakeholders, on managing the decentralization process.